2016
DOI: 10.1038/srep39136
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Mesoporous α-Fe2O3 Nanoparticles by Non-ionic Soft Template and Their Applications to Heavy Oil Upgrading

Abstract: This paper reports the synthetic route of 3-D network shape α-Fe2O3 from aqueous solutions of iron precursor using a non-ionic polymeric soft-template, Pluronic P123. During the synthesis of α-Fe2O3, particle sizes, crystal phases and morphologies were significantly influenced by pH, concentrations of precursor and template. The unique shape of worm-like hematite was obtained only when a starting solution was prepared by a weakly basic pH condition and a very specific composition of constituents. The synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 42 publications
3
14
1
Order By: Relevance
“…In other words, the Type IV isotherms with H 1 hysteresis are clearly observed for all synthesized samples, except for FCC CP and FCM CP having a Type I isotherm. Interestingly, FCC SG does not have a well-defined Type IV pattern, and this behavior corresponds to those of mesopores and macropores presence [20,21], as already suggested by SEM (Figure 1c included). Additionally, the hysteresis loop for the FCC SG is not well established, presumably because of the presence of inter-particle void space.…”
Section: Physicochemical Properties Of the Synthesized Solidssupporting
confidence: 64%
See 3 more Smart Citations
“…In other words, the Type IV isotherms with H 1 hysteresis are clearly observed for all synthesized samples, except for FCC CP and FCM CP having a Type I isotherm. Interestingly, FCC SG does not have a well-defined Type IV pattern, and this behavior corresponds to those of mesopores and macropores presence [20,21], as already suggested by SEM (Figure 1c included). Additionally, the hysteresis loop for the FCC SG is not well established, presumably because of the presence of inter-particle void space.…”
Section: Physicochemical Properties Of the Synthesized Solidssupporting
confidence: 64%
“…This nanoarchitecture is duly reflected by the XAD-16 resin template hollow sphere morphology [20,21]. Some of the spheres were unbroken, indicating that the metal precursors infiltrated successfully into the spheres, whilst other spheroids were cracked because the calcination process burned the template (Figure 1a included, left side).…”
Section: Physicochemical Properties Of the Synthesized Solidsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 2, 2 broad peaks at approximately 2 θ = 34.4 and 62.8 were observed, and these were assigned to the (110) and (115) planes of 2‐line ferrihydrite (2LFh) (JCPDS card number 29‐0712). No characteristic peaks from the impurities were detected, and this coincided with previous reports and confirmed that the product was 2LFh . Based on the number of peaks resolved from powder XRD patterns, 2 types of ferrihydrite are commonly distinguished, namely 2LFh and 6‐line ferrihydrite (6LFh) .…”
Section: Resultssupporting
confidence: 90%